Optimalisasi Penggunaan Human Resource Information System (HRIS) pada Human Capital Administration of The Foundation - Andani, Julina; Purbasari, RR Niken (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2024)
The Foundation is a non-profit organization that focuses on education and empowerment of women in micro-enterprises (MSMEs). The Foundation has several community activity programs such as scholarship programs, batik learning houses, learning house programs for underprivileged community groups, etc. Community Service Activities carried out by STIE Trisakti at The Foundation aim to help organizations improve the accuracy and completeness of data on the HRIS (Human Resource Information System) used by The Foundation so that the process of managing Human Resource (HR) management activities becomes more efficient and appropriate. The STIE Trisakti Community Service Team together with The Foundation team carry out activities to apply management science, especially human resource management, to optimize the use of HRIS as a solution for managing organizational HR by updating employee data through the process of collecting the latest employee data and filling out employee data update forms continuously. The use of HRIS in routine activities is the responsibility of the HC administration unit so that the available data is accurate and can minimize errors that generally occur in the process of organizational HR management activities. Accurate employee data information is an important part of the HR management process to achieve efficiency and effectiveness in achieving success goals.